Macro ingredients as markers of the quality of mixing feed Macro ingredientes como indicadores da qualidade de mistura de ra̧ões1 - Biazzi H.M.* (2014)
A study was conducted to evaluate the use of macro ingredients as markers of the quality of mixed feeds. Were used: popcorn grain, sorghum, millet, rice colored and purple corn grinded (0.5% added to the diet, substituting grind corn) and coarse limestone sieved through sieve n° 10 ABNT with 2 mm (added in 0.5% in the diet, substituting finely ground limestone). Microtracer F-Red was used as a method of reference. It was used a Y-type mixer (capacity of 5,000 cm3), and produced 1 kg of feed per repetition. It was adopted six mixing times (10 seconds, 1, 6, 11, 16 and 21 minutes) and five particle size of corn (386, 513, 610, 731 and 839 μm), amounting 30 treatments with three repetitions for each treatment. Where collected 12 samples, for each replicate, to measurement of the markers and determination of the coefficient of variation (CV). A quadratic effect with minimum point for the CV was observed for all markers with the increasing of the mixing time. There was no effect of the particle size of corn for the coefficients of variation of coarse limestone and millet. There was a quadratic response of the particle size of corn for the coefficients of variation of purple corn and popcorn grain and linear effect for the colored rice, sorghum and reference method. The particle size of corn changed the time needed to reduce the CV of the markers: colored rice, milled purple corn, popcorn, sorghum and microtracer. The use of alternative markers has shown that it is a promising tool for the determination of the optimum mixing time, especially millet and limestone, that showed the highest correlations with the reference method.